Red wine lees lysis induced by combining mechanical and physical treatments to enhance the extraction of polyphenols and proteins - Mihaela Cotârleț; Aida Mihaela Vasile; Mihaela Turturică; Gabriela Râpeanu; Adrian Cîrciumaru; Nicoleta Stănciuc; Gabriela Elena Bahrim (Applied Food Research)
This research explored the potential of residual wine lees to enhance the extraction of polyphenols and proteins using different inactivation methods, such as mechanical and physical treatments, from the perspective of integrating in biocomposites for soil treatment. Different combination of methods were used, such as freeze-drying, pestle, ultrasound-thermal treatments at different combination of temperature and time. The results showed that complete inactivation of cells were obtained by ultrasound treatment at temperatures higher than 70 °C for 30–60 min. The variant treated by ultrasound at 80 °C for 30 min showed the highest total polyphenols and flavonoids contents of 2.90±0.13 mg GAE/g DM and 2.96±0.11 mg CE/g DM, respectively, leading to a capacity to inhibit the free radicals of 69.63±0.16 %. The break of cells walls lead to an increase in protein content up to 2.37±0.08 mg/g DM. The cromatographic analysis revealed a different polyphenolic profile, depending on the type and the intensity of the inactivation treatments. Gallic acid and (-)-epigallocatechin were the common compounds in all samples, with the highest content in sample treated by ultrasound at 70 °C for 1 h (22.58±0.71 ng/mL). The highest concentration in (-)-epigallocatechin was observed in the samples ultrasound treated at 70 °C for 1 h (257.51±0.70 ng/mL) and at 80 °C for 30 min (207.65±0.69 ng/mL). A prebiotic effect on Bacillus B5 strain with a 1 log increase was found for the sample treated by ultrasound at 80 °C.